Program and abstracts from the 24th Fungal Genetics Conference - Fungal Genetics Conference (Fungal Genetics Reports, 2007)
Abstracts of the plenary and poster sessions from the 24th Fungal Genetics Conference, March 20-25, 2007, Pacific Grove, CA.